Different Agroresidues Used in Solid Substrate Fermentation for ?-Amylase Production by Bacillus subtilis-239: Agroresidue Fermentation for Amylase Production (Biological Sciences - PJSIR, 2008)
The best mass ratio for agroresidue fermentation for a-amylase production by locally isolated Bacillus subtilis-239 was found to be wheat bran to rice bran 2:1 with 70% initial moisture content for 60 h incubation time. Among different inorganic nitrogen sources supplemented, sodium nitrate and ammonium chloride (0.5% w/w) increased the enzyme yield upto 178 U/ml and 176 U/ml, respectively, whereas all the organic nitrogen sources decreased the enzyme production. Addition of glucose (1% w/w) as a carbon source enhanced a-amylase synthesis to 185 U/ml as compared to the control (134  U/ml).